Susceptibility to coronary artery disease and diabetes is encoded by distinct, tightly linked SNPs in the ANRIL locus on chromosome 9p - Broadbent, H; Peden, J; Lorkowski, S; Goel, A; Ongen, H; Green, F; Clarke, R; Collins, R; Franzosi, M; Tognoni, G; Seedorf, U; Rust, S; et al. (Oxford University Press, 2008)
Genome-wide association studies have identified a region on chromosome 9p that is associated with coronary artery disease (CAD). The region is also associated with type 2 diabetes (T2D), a risk factor for CAD, although different SNPs were reported to be associated to each disease in separate studies. We have undertaken a case-control study in 4251 CAD cases and 4443 controls in four European populations using previously reported ('literature') and tagging SNPs. We replicated the literature SNPs (P = 8 x 10^-13; OR = 1.29; 95% CI: 1.20- 1.38) and showed that the strong consistent association detected by these SNPs is a consequence of a 'ying-yang' haplotype pattern spanning 53 kb. There was no evidence of additional CAD susceptibility alleles over the major risk haplotype. CAD patients without myocardial infarction (MI) showed a trend towards stronger association than MI patients. The CAD susceptibility conferred by this locus did not differ by sex, age, smoking, obesity, hypertension or diabetes. A simultaneous test of CAD and diabetes susceptibility with CAD and T2D-associated SNPs indicated that these associations were independent of each other. Moreover, this region was not associated with differences in plasma levels of low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, fibrinogen, albumin, uric acid, bilirubin or homocysteine, although the CAD-high-risk allele was paradoxically associated with lower triglycerine levels. A large antisense non-coding RNA gene (ANRIL) collocates with the high-risk haplotype, is expressed in tissues and cell types that are affected by atherosclerosis and is a prime candidate gene for the chromosome 9p CAD locus.